Flexible resistive random access memory devices by using NiOx/GaN microdisk arrays fabricated on graphene films. (21st April 2017) - Lee, Keundong; Park, Jong-woo; Tchoe, Youngbin; Yoon, Jiyoung; Chung, Kunook; Yoon, Hosang; Lee, Sangik; Yoon, Chansoo; Ho Park, Bae; Yi, Gyu-Chul
Abstract: We report flexible resistive random access memory (ReRAM) arrays fabricated by using NiO x /GaN microdisk arrays on graphene films. The ReRAM device was created from discrete GaN microdisk arrays grown on graphene films produced by chemical vapor deposition, followed by deposition of NiO x thin layers and Au metal contacts. The microdisk ReRAM arrays were transferred to flexible plastic substrates by a simple lift-off technique. The electrical and memory characteristics of the ReRAM devices were investigated under bending conditions. Resistive switching characteristics, including cumulative probability, endurance, and retention, were measured. After 1000 bending repetitions, no significant change in the device characteristics was observed. The flexible ReRAM devices, constructed by using only inorganic materials, operated reliably at temperatures as high as 180 °C.